The Implementation of Child-Centered Group Play Therapy in Social Skill Learning for Slow learner - Dahlia Novarianing Asri; Ratih Christiana; Septalia Fajar Dwi Ismanda (Universitas PGRI Yogyakarta, 2026)
Slow learners experience substantial deficits in social interaction, yet interventions targeting their social skills development remain underexplored. This study investigated the implementation of Child-Centered Group Play Therapy (CCGPT) to enhance social skills among slow learners in an inclusive elementary school. A qualitative descriptive approach was employed over two months at Bangsri 02 Elementary School, Magetan Regency, Indonesia. Eight slow learners (four male, four female) in grades V and VI were purposively selected. Data were collected through passive participant observation, in-depth interviews with special assistant teachers, and documentation. Analysis followed Miles and Huberman's interactive model, comprising data reduction, presentation, and conclusion drawing. Teachers demonstrated adequate competency in implementing the five-stage CCGPT protocol. Of 31 social skill indicators measured across cooperation, assertion, responsibility, empathy, and self-control domains, 27 indicators (87.01%) were achieved. However, four indicators remained underdeveloped: self-confidence in interaction, appropriate emotional expression, emotional control, and proper speech tone. Implementation challenges included teachers’ limited psychological backgrounds, inadequate facilities, and cognitive constraints among slow learners. CCGPT shows promise for improving social skills in slow learners. Recommendations include specialized teacher training, provision of therapy rooms, and future research incorporating art elements to enhance emotional expression and self-confidence. Keywords: child-centered group play therapy, social skills; slow learner, inclusive education, qualitative study